Role of Corporate Governance in the Voluntary Disclosure of Intellectual Capital - Kamat, G Bharathi (International Research Journal of Business Studies, 2019)
The research on intangible assets and its contribution to the value creation of the firms has received significant attention in recent times. This paper attempts to estimate and analyse the nature and extent of overall Intellectual Capital Disclosure (ICD) and its sub-components in the annual reports of Information Technology (IT) industry in India for the FY 2017-18. It also attempts to examine whether Corporate Governance Characteristics of these firms influence their ICD. Multiple linear regression analysis is used to evaluate the data on information technology Industry. IT firms in India disclose a very high extent of Human capital; whereas the nature of disclosure is high in case of Structural Capital. The empirical evidence suggests that board size, its independence and ownership pattern of the firm play a significant role in the extent of overall intellectual capital disclosures in Indian IT firms. The result on impact of corporate governance characteristics varies with respect to the IC sub-components.